PENGARUH PEMBIAYAAN BAGI HASIL, PEMBIAYAAN JUAL BELI, FINANCING TO DEPOSIT RATIO (FDR) TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) PERIODE 2015-2017 - Yuniatin Trisnawati D.K.W; Muhammad Ridho P (AKTUAL, 2019)
The Influence of Financing for results, Financing and selling and Financing To Deposit Ratio (FDR) against profitability At Sharia Bank in Indonesia which listed in the Indonesia stock exchange (IDX) in period 2015-2017. This study aims to examine and obtain empirical evidence that Profit Sharing Financing, Buying and Selling Financing, Financing to Deposit Ratio (FDR) significantly influence the Profitability (ROA) of Islamic Commercial Banks in Indonesia in 2015-2017. This research is quantitative descriptive. The data used in the form of the bank's annual financial statements are sampled in research with a period of three years. The sample of this study was determined by simple random sampling method to obtain 11 Islamic Commercial Banks. The type of data used is secondary data obtained from the websites of each bank and www.idx.co.id. The analytical method used is statistical description, multiple linear regression, classical assumption test and hypothesis test. The results of this research hypothesis testing indicate that the profit sharing financing variable has a negative but not significant effect, the buying and selling financing variable has a positive but notsignificant effect and the variable Financing to Deposit Ratio (FDR) has a negative but significant effect on profitability (ROA). The result of adjusted R2 analysis is 23% the influence given by the independent variable(profit sharing financing, buying and selling financing and FDR) to the dependent variable profitability (ROA). The remaining 77% is influenced by variables outside the variables studied.Keywords: Profitability, profit sharing financing, buying and selling financing and FDR.